PENGARUH PEMBERIAN STIMULASI SENSOMOTOR TERHADAP TINGKAT AROUSAL DAN ATENSI ANAK NORMAL USIA 6-8 TAHUN DI SDN PASIR PUTIH 01 KEC. SAWANGAN DEPOK - Emi Nurjasmi; Ari Sudarsono (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
Ability to follow and concentrate forms the basis for most functions - cognitive function. One of stimulation that can improve attention (attention) is sensomotor stimulation which is stimulation through general sensory innervation system (touch, taste, motion, vibration, temperature, and pain) and special sensory fibers (visual, auditory, kinesthetic) with the aim to improve entire central admission system in the cerebral cortex receptive. In term of the importance of children having optimal levels of arousal and attention in a process of learning in elementary school education encourages researchers to conduct this research. This study is a quasi-experimental study in which researchers intervened sensomotor stimulation with various forms of activities that stimulate different senses sensory. The purpose of this study is to look at the effectiveness of sensomotor stimulation in normal children aged 6-8 years attending primary school. The study population was normal children aged 6-8 years in SDN. 01 Pasir Putih Kec.Sawangan. The number of samples is in accordance with a population that is 68 people (purposive sample) using pretest and posttest control group which is simple experimental design, with the initial measurement or observation before treatment is given. One group of subjects was given treatment, while the other group was given no treatment. Results showed Stroop test scores before and after treatment in group I were analyzed by Paired Samples Test showed that sensomotor stimulation produces significantly changes on Stroop test scores (p <0,05). But there was no significant difference (p >0,05) between groups I given sensomotor stimulation and group II were given free play.